2002
DOI: 10.1148/radiol.2232010665
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic MR Imaging of the Pelvic Floor Performed with Patient Sitting in an Open-Magnet Unit versus with Patient Supine in a Closed-Magnet Unit

Abstract: Dynamic supine MR imaging performed with a closed-configuration unit before and after rectal contrast agent administration appears to be an alternative to sitting MR defecography performed with an open-configuration unit for diagnosis of clinically relevant pelvic floor abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
9

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(118 citation statements)
references
References 18 publications
2
106
0
9
Order By: Relevance
“…We minimized this limitation by careful coaching the woman to achieve the maximal prolapse and reviewed all the dynamic video clips to make sure that Valsalva was performed correctly. In the past, researchers have compared supine dynamic MRI with those performed in a sitting position in an open configuration scanner and found supine scans during straining to be comparable in documenting pelvic floor movement [26,27]. An additional limitation is represented by the example in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We minimized this limitation by careful coaching the woman to achieve the maximal prolapse and reviewed all the dynamic video clips to make sure that Valsalva was performed correctly. In the past, researchers have compared supine dynamic MRI with those performed in a sitting position in an open configuration scanner and found supine scans during straining to be comparable in documenting pelvic floor movement [26,27]. An additional limitation is represented by the example in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, patient positioning, force of valsalva, and bladder distention have been shown to affect the severity of POP [8][9][10][11][12]. Our POP-Q exams were performed in the supine position with the patient straining.…”
Section: Discussionmentioning
confidence: 99%
“…7,11 A further limitation of the supine position is represented by the difficulty of carrying out the voiding phase, which is the most important phase for correct clinicalediagnostic assessment. In the present population, only 28 of the 49 patients enrolled managed to complete the MRD in the supine position, whereas all patients performed the voiding phase in the erect position.…”
Section: Discussionmentioning
confidence: 99%